Factors predicting clinical outcomes from 494 vitrified oocyte donation cycles at a UK-regulated egg bank. Issue 3 (September 2021) - Pataia, Vanessa; Nair, Shailaja; Wolska, Marta; Linara-Demakakou, Elena; Shah, Trina; Lamanna, Giuseppina; Macklon, Nick; Ahuja, Kamal K.
Abstract: Research question: Do donor age, AMH, AFC, BMI and reproductive history predict response to ovarian stimulation? Do donor and recipient clinical markers and embryology parameters predict recipient pregnancy and live birth? Design: Retrospective cohort study of 494 altruistic oocyte donors aged 18–35 years; 340 were matched to 559 recipients. Predictors of donor total oocyte yield and total mature oocyte yield were identified. Total and mature oocyte number were compared according to stratified donor AMH and age. Donor, recipient and embryology parameters predictive of recipient primary outcomes (clinical pregnancy and live birth) were identified. Results: Donor age and AMH predicted total oocyte yield ( P = 0.030 and P < 0.001)) and total mature oocyte yield ( P = 0.011 and P < 0.001). Donors aged 30–35 years with AMH 15–29.9 pmol/l had lower total oocyte yield ( P = 0.004) and mature oocyte yield ( P < 0.001) than donors aged 18–24 years. Up to an AMH threshold of 39.9 pmol/l, increasing AMH levels predicted higher total oocyte yield (<15 pmol/l versus 15–29.9 pmol/l, P = 0.001; 15–29.9 pmol/l versus 30–39.9 pmol/l, P < 0.001; 30–39.9pmol/l versus ≥ 40 pmol/l, P = 1.0) and mature oocyte yield (<15 pmol/l versus 15–29.9 pmol/l, P = 0.005; 15–29.9 pmol/l versus 30–39.9 pmol/l, P = 0.006; 30–39.9 pmol/l versus ≥40 pmol/l, P = 1.0). In recipients, the rate of transferrable embryos per oocytes received, fertilized and number of embryo transfers needed to achieve the primary outcome were predictors of cumulative clinical pregnancy ( P = 0.011, P = 0.017 and P < 0.001) and live birth ( P = 0.008, P = 0.012 and P < 0.001) rates. Recipient BMI ( P = 0.024) and previous miscarriages ( P = 0.045) were predictors of cumulative live birth rate. Donor age 18–22 years was associated with a lower incidence of recipient clinical pregnancy ( P = 0.004) and live birth ( P = 0.001) after the first embryo transfer versus donor age 23–29 years. Conclusions: Donor age and AMH are independent predictors of oocyte yield. Raised recipient BMI and history of miscarriages reduce cumulative live birth rates, which may be increased by selecting donors aged 23–29 years, instead of younger donors.